Kebab Sebagai Inovasi Produk Makanan Yang Berguna Sebagai Peningkatan Gizi Pada Anak-Anak Di Desa Bontokassi Kecamatan Parangloe Kabupaten Gowa - Suriyanti Suriyanti; Niniek F. Lantara (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
indonesia has many diverse vegetable plants. Vegetables are plants that are often used as ingredients to complement rice and side dishes. Vegetables are rich in fiber, vitamins, and minerals so they are very good to consume. The benefits of lettuce can be felt when consumed regularly. This green leafy vegetable is low in calories and will not be a problem when consumed in large quantities. Kebab is made from vegetables, chicken, cheese, tomatoes, lettuce leaves. Kebab bread is the latest innovation that is rarely found on the market which is made from vegetables and white bread. Thus we innovate to create nutritious food for children as an alternative food. This new innovation can also increase children's nutrition because it is made from vegetables where vegetables are very much needed by the body, especially children, so that children's nutrition is sufficient. The business of making Kebabs made from vegetables, fruit, cheese, chicken meat increases the selling power of Kebab products. This Kebab product manufacturing business will be marketed in the Bontokassi area and will be developed outside the Bontokassi area. Kebab has a fairly high business opportunity because: (1) Many people, especially children, like this type of food; (2) Raw materials that are easy to obtain; (3) An alternative vegetable substitute for children who do not like vegetables; (4) In making Kebab does not require special skills; (5) From teenagers to adults can make this product; (6) Not many people sell this product. The target of this product is small children and teenagers who do not like vegetables, especially carrots and lettuce, because this product has an affordable price and has great benefits.